Perbandingan Efektivitas Pendidikan Kesehatan Antara Media Cetak Dan Media Elektronik Terhadap Mual Muntah Pada Ibu Hamil - Tri Nur Jayanti; Yanti Hermayanti; Tetti Solehati (Jurnal Keperawatan Muhammadiyah, 2021)
Background:  Nausea and Vomiting of Pregnancy (NVP) is one of the symptoms that are often experienced by pregnant women. This condition is physiological, but if it is unhandled it would be pathological and adversely affect the women and fetus. Health education is considered to be able to improve the knowledge and skill of women in overcoming these symptomps.Objective:  To determine the comparison of health education effectiveness between print media and electronic media on knowledge, behavior, and the level of nausea and vomiting in pregnant women. Methods:  This study was a quasi-experimental research with two groups of pre-test and post-test designs. It included 56 pregnant women with NVP which were taken by quota sampling at Pindad and Sartika Asih Hospital in October-December 2019. The data were divided into two groups. Group A (GA) received health education through print media, Group B (GB) through electronic media. The measurement used questionnaires of knowledge about NVP, behavior in handling NVP, and PUQE-24 were repeated and analyzed using the Friedman, Post Hoc, and Mann Whitney tests.Results:  There was a significant difference in the mean of knowledge, behavior, and the level of nausea and vomiting between before and after intervention in both groups. Differences in the mean of knowledge, behavior, and the level of nausea and vomiting in GA were the same as in GB, but decrease the levels of nausea and vomiting were found to be faster in GA.Conclusion:  Print media and electronic media are equally effective for increasing knowledge and behavior and decreasing the level of nausea and vomiting in pregnant women. Further research needs to determine the effectiveness of this intervention on the quality of life of pregnant women so that the change can be known holistically.